Teknik Pelestarian Habitat Penyu Lekang (Lepidochelys olivacea) di Kawasan Konservasi Penyu Kurma Asih, Desa Perancak, Kabupaten Jembrana, Bali - Rahman Jayawangsa; Larasati, Chandrika Eka (Jurnal Ilmu Kelautan Lesser Sunda, 2024)
The Olive Ridley Sea Turtle population in Indonesia continues to decline due to natural and human factors. So it is necessary to conserve it so that its population does not become extinct. One of the conservation areas that protect sea turtle eggs is in the Kurma Asih Conservation Area, Perancak Village, Jembrana Regency, Bali. This study aims to observe and collect physical data on beach habitats that are considered suitable as sea turtle nesting habitats and collect data on Olive Ridley Sea Turtle tracks and nests in Perancak Village. Data collection is done by going directly to the field (monitoring) to find out the location of nesting turtles. The data required are beach characteristics, characteristics of nests and potential predators of eggs and turtle identification. The results showed that the characteristics of the turtle nesting beach were that there were 7 types of vegetation identified such as waru trees, coconut trees, pandanus trees, katang-katang plants, weeds, bushes and rolling plants, the texture of the beach sand sediments was fine and black in color. 19 individual Olive Ridley sea turtles were found, with 22 nests, and 23 turtle tracks. There are human and dog footprints around the coastline that are potential predators for sea turtle eggs. The results of this observation can be recommended to those who need to keep the location well maintained, so that sea turtles will always land